THE IMPACT OF ZONING SYSTEMS ON STUDENTS MOTIVATION IN SMPN 1 MAJENANG - Zubaedah Nur Fajriah; Pipit Muliyah; Atabik (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
Motivation to learn is one of the factors that influence learning success. The greater the motivation to learn, the greater the opportunity to achieve learning success. The zoning system is a policy for admitting new students by using the distance between the studeZnt's residence and the school. With this system, the implementation of the admission of new students is no longer seen in terms of value. So the zoning system will undermine learning motivation. Because to enter your favorite school, you don't need high grades and abilities. The formulation of the problem discussed is how the zoning system is implemented in SMP Negeri 1 Majenang, what factors affect student motivation, how is the impact of the zoning system on the learning motivation of SMP Negeri 1 Majenang students. The aim is to provide an overview of the impact of the zoning system on student motivation at SMP Negeri 1 Majenang. This type of research is field research with a qualitative approach. Data collection techniques in the form of questionnaires, interviews, observation. The analysis technique uses descriptive qualitative analysis. The results of the research on the impact of the zoning system on the learning motivation of students of SMP Negeri 1 Majenang as a whole are still relatively good with a percentage of 65%. Factors that influence student learning motivation consist of internal and external factors. The grouping system implemented at SMP Negeri 1 Majenang makes learning more effective and efficient.